2018
DOI: 10.1152/japplphysiol.00623.2018
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of regional cerebral blood flow during graded reflex-mediated sympathetic activation via lower body negative pressure

Abstract: The role of the sympathetic nervous system in cerebral blood flow (CBF) regulation remains unclear. Previous studies have primarily measured middle cerebral artery blood velocity to assess CBF. Recently, there has been a transition towards measuring internal carotid artery (ICA) and vertebral artery (VA) blood flow using duplex Doppler ultrasound. Given that the VA supplies autonomic control centers in the brainstem, we hypothesized that graded sympathetic activation via lower body negative pressure (LBNP) wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In the present study, increases in IOP (P Ͻ 0.001; Table 1), an indirect index of ICP, might have been expected to decrease cerebral perfusion pressure and therefore perfusion during HDT. However, both ICA and VA blood flows were well maintained during mild body position change, as found in previous studies (12,26,41), thus suggesting that cerebral perfusion pressure was well maintained. Similarly, the previous study of Petersen et al (32) demonstrated that regulation of ABP maintained cerebral perfusion pressure regardless of body position.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, increases in IOP (P Ͻ 0.001; Table 1), an indirect index of ICP, might have been expected to decrease cerebral perfusion pressure and therefore perfusion during HDT. However, both ICA and VA blood flows were well maintained during mild body position change, as found in previous studies (12,26,41), thus suggesting that cerebral perfusion pressure was well maintained. Similarly, the previous study of Petersen et al (32) demonstrated that regulation of ABP maintained cerebral perfusion pressure regardless of body position.…”
Section: Discussionsupporting
confidence: 85%
“…MCAv resting values during baseline were only significantly increased in 5,500 m HH when compared to NN and 3,000 m HH (Table ). MCAv was logically decreased during hyperventilation due to the hypocapnia‐induced vasoconstriction (Kaur et al, ). Then, hypercapnia triggers cerebral vasodilation, which induces an increase in MCAv.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were: 1) inability of study staff to acquire signal of the MCA using transcranial Doppler ultrasound, 2) inability to perform the alternating leg movements on the seated recumbent stepper 3) diagnosis of Parkinson's disease, mild cognitive impairment, Alzheimer's disease or multiple sclerosis, 4) pulmonary disease or dependency on supplemental oxygen or 5) diagnosis of myocardial infarction or heart failure. Before reporting to the laboratory at the University of Kansas Medical Center, participants were asked to abstain from food for two hours (Fisher et al 2008, Kaur et al 2018, Ogoh et al 2005, caffeine for a minimum of six hours, (Ainslie et al 2008) and vigorous exercise for twelve hours prior to testing. (Ogoh et al 2005, Billinger, Craig, et al 2017 All female participants were verbally questioned regarding menstrual status.…”
Section: Participant Criteriamentioning
confidence: 99%